Development of a Learning Module for Road and Bridge Design Modeling with Augmented Reality Integration - Pratiwi, Wikanti; Qudus, Nur; Anis, Samsudin (Journal of Vocational and Career Education, 2025)
The average learning outcomes of eleventh-grade students in 2024 indicate a disparity between psychomotor skills (88), which are higher, and cognitive skills (83). Augmented Reality (AR)-based learning is expected to have the potential to enhance the conceptual abilities of vocational high school students, who tend to be less developed than their psychomotor skills. The purpose of this study was to analyze the feasibility of the module, evaluate its effectiveness, and assess the improvement of students’ cognitive abilities. This research employed the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The findings revealed that the AR-based module was deemed feasible by both material experts and media experts, with a CVR value of 1. Of the 37 cognitive test items developed, 26 were found to be valid and used in the study, while 11 questions were excluded due to invalidity. The reliability coefficient of 0.854 indicated very high instrument consistency. Based on the N-Gain test, the experimental class recorded an improvement of 0.61 (moderately effective), while the control class achieved only 0.21 (ineffective). These results demonstrate that the AR-based module is more effective in enhancing students’ cognitive abilities compared to conventional learning methods.